Hubungan Dukungan Keluarga Dengan Tingkat Kecemasan Ibu Pada Balita Yang Mengalami Pneumonia Di Wilayah Kerja Puskesmas Kemangkon - Fatikasari, Lutfi; Solikhah, Umi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
ABSTRACTPneumonia is an acute lower respiratory tract infection that affects lung tissue with symptoms of coughing, shortness of breath, ronchi. Pneumonia patients under five in Purbalingga in 2018 found 1,787 cases or 61.40%. Family support will be increasingly needed when someone is experiencing problems or illnesses, in this case, the role of the family is necessary as going through difficult times quickly. Good family support for mothers of children with pneumonia can reduce anxiety. Mothers need family support to care for their children. Research purpose to determine the correlation between family support and mothers' anxiety level in toddlers with pneumonia in the working area of Public Health Center of Kemangkon. It was a quantitative descriptive study with a cross-sectional method. The samples were collected by simple random sampling of 42 respondents. The results discovered that there were 19 respondents (45.2%) who were in their late teens. There were 25 respondents (59.5%) who graduated from junior high school. There were 20 respondents (47.6%) who were mostly housewives. There were 29 respondents (69%) who got good family support and there were 22 respondents (52.4%) who felt anxious. There is the relationship between family support and mothers' anxiety level in toddlers with pneumonia in the working area of Public Health Center of Kemangkon with (Ï-value = 0.001).